PELATIHAN UNTUK PEMBERDAYAAN PROMOSI UMKM BINAAN BUMDES SERDANG TIRTA KENCANA KECAMATAN LEGOK, KABUPATEN TANGERANG - Purba, Florensa Rosani; Putra Adirinekso, Gidion; Marvianta, YB. Andre; Assa, Adrie F. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
One of the problems found in BUMDes Serdang Tirta Kencana, Serdang Wetan Village is how MSMEs can be more advanced, in addition to developing the use of Embung as an effort to improve the welfare of the surrounding community. The efforts made in Pk Mini are only part of several empowerment plans for improving the welfare of the community and STK BUMDes. Promotion through social media is one of the efforts to increase their income. Therefore, training is carried out to photograph products and videos that will be used to promote their products. The enthusiastic response and response was very real. This is shown by the preparation before training, the implementation of training, to the results of photos and videos produced. Collaboration to advance MSMEs and BUMDes is a strong basis for the community to participate in the development of improving their welfare.